Marine Productivity: Perturbations and Resilience of Socio-ecosystems Proceedings of the 15th French-Japanese Oceanography Symposium - Ceccaldi, Hubert-Jean.; Hénocque, Yves.; Koike, Yasuyuki; Komatsu, Teruhisa; Stora, Georges; Tusseau-Vuillemin, Marie-Hélène.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2015)
The 15th Franco-Japanese Symposium of Oceanography “Marine Productivity, Perturbations and Resilience of Socio-Ecosystems,” organized by the long-standing partners Société franco-japonaise d'Océanographie de France and Société franco-japonaise d'Océanographie du Japon, reviewed the impacts of natural (storms, typhoons, earthquakes, tsunamis, etc.) and man-made (pollution, buildings in coastal areas, aquaculture, tourism, sports, diving, etc.) perturbations inflicted on coastal and marine environments. The Symposium examined the resilience of affected socio-ecosystems along with governance responses for these global/local environments. This book collects 43 selected papers, written by experts from numerous universities and research institutes in both countries. It addresses the needs of marine sciences researchers (natural and social sciences), decision-makers and coastal zone managers, and other stakeholders involved in coastal and marine socio-ecosystems.
Part I: Special Introductory Communication - Part II: Natural Disturbances -- Part III: Anthropogenic Disturbances -- Part IV: Ecosystem Based Approach -- Part V: People, Institutions and the Sea -- Part VI: Status and Future of Marine Protected Areas -- Part VII: Round Table: Sato-umi, the Wealth of the Commons -- Part VIII: Short and Preliminary Communications.
Keywords: Oceanography; Coasts; Oceanography; Coastal Sciences